IDENTIFIKASI GANGGUAN KONEKSI JARINGAN INTERNET PADA INDIHOME PLASA TELKOM MUARA TEWEH BERBSASIS SISTEM PAKAR - Hartini, Hartini Tini; Teruna, Juli Chandra; Swastina, Liliana (Universitas Putera Batam, 2022)
Plasa Telkom Muara Teweh is one of the shelters of PT. Telekomunikasi Indonesia in charge of providing telecommunications services to the public. The new product under the name IndiHome is one of the programs from Telkom's main project by cooperating with a number of communication technology developments to build a digital concept house. In connection with the constant requests for installation of IndiHome services, complaints or reports will often be found in the form of internet network connection disturbances from IndiHome customers. At this time the disturbance report received by the technician is in the form of not being able to connect to the internet network. Therefore, technicians always contact the customer first by telephone before going to the customer's house to fix it. From this interaction, the technician asks questions in the form of what indicator lights are on and off on the subscriber's modem. The result is that technicians are only limited to recording disturbance reports manually without being able to provide direct solutions. This ability can be applied in the form of computer software using an expert system. The expert system method used is forward chaining where later this method is used to find facts about internet disturbances that occur from browsing the modem used by customers to symptoms of internet disturbances, so that solutions are found for these internet disturbances.